PERAN INTERNATIONAL LABOUR ORGANIZATION (ILO) DALAM PENYELESAIAN HUBUNGAN INDUSTRI DI INDONESIA - , Annisa Febrianty Rahayu; Eka Yulyana (Moderat : Jurnal Ilmiah Ilmu Pemerintahan, 2024)
This research discusses the role of the government in resolving labor disputes in Indonesia, with a focus on issues related to age, education, and experience criteria in the context of employment. This research uses a descriptive research method with a qualitative approach. The data collection technique used in this research is adjusted to the research objective, which is Literature Study or Library Study. According to Zed and Merfianora (2019), Library Research, which is the literature search, is not the initial step in preparing the research framework, but rather simultaneously utilizes several library sources. In this research, the theory of international organizations is used. International organizations can be defined as a continuous formal structure whose formation is based on agreements among its members. (Archer et al., 1893). Labor disputes are conflicts between workers and employers that arise due to differences in opinion regarding rights, obligations, and working conditions. The government plays an important role in handling labor disputes to achieve justice in the workplace. However, various issues arise related to age and education criteria in the resolution of labor disputes. First, age criteria become an obstacle in assessing workers' rights and responsibilities. Some policies that do not align with the dynamics of workers' ages can lead to inequality and injustice. Therefore, it is necessary to develop guidelines that are more inclusive of age differences in the workplace. Secondly, education is a factor that influences workers' understanding of their rights and obligations. The government needs to improve labor law literacy among workers. The government needs to establish a fair and transparent mechanism to assess work experience and prevent discrimination. By understanding the issues related to age, education, and experience criteria in labor dispute resolution, the government can develop more effective and inclusive policies. These steps are expected to enhance fairness, harmony, and productivity in the Indonesian labor market.